Measurement of thermometer using automated system - Pradeep Kumar, S; Shanmugasundaram, N; N. Ganesh, E (International Journal of Engineering and Technology, 2018)
Calibration of thermometers is time- consuming process that requires short-term temperature stability during multiple measurements at given temperature points. In most laboratories, thermometer calibration process is not automated, requiring the presence of the laboratory assistant during the calibration and for the subsequent calculation of the measurement uncertainty. In this paper, an automated system for calibration of thermometers is presented. The system enables the entire calibration process to be computer driven, after setting calibration parameters. The details are presented on an example of a furnace for temperatures up to 1 000 ° C. The review of the metrology software is given